Adherence partners are an acceptable behaviour change strategy to support calcium and iron‐folic acid supplementation among pregnant women in Ethiopia and Kenya. Issue 3 (9th August 2016) - Martin, Stephanie L.; Omotayo, Moshood O.; Chapleau, Gina M.; Stoltzfus, Rebecca J.; Birhanu, Zewdie; Ortolano, Stephanie E.; Pelto, Gretel H.; Dickin, Katherine L.
Abstract: Antenatal calcium and iron‐folic acid (IFA) supplementation can reduce maternal mortality and morbidity. Yet, even when pregnant women have a stable supply of supplements, forgetting is often a barrier to adherence. We assessed the acceptability of adherence partners to support calcium and IFA supplementation among pregnant women in Kenya and Ethiopia. Adherence partners are a behaviour change strategy to improve adherence, where pregnant women are counselled to select a partner (e.g. spouse, relative) to remind them to take their supplements. We conducted trials of improved practices, a formative research method that follows participants over time as they try a new behaviour. We provided pregnant women in Ethiopia ( n  = 50) and Kenya ( n  = 35) with calcium and IFA supplements and counselling, and suggested selecting an adherence partner. For each participant, we conducted semi‐structured interviews about acceptability and adherence during four interviews over six weeks. We analysed interview transcripts thematically and tallied numerical data. In Kenya, 28 of 35 women agreed to try an adherence partner; almost all selected their husbands. In Ethiopia, 42 of 50 women agreed to try an adherence partner; half asked their husbands, others asked children or relatives. Most women who did not select adherence partners reported not needing help or not having anyone to ask. Participants reported adherence partners reminded and encouraged them, brought supplements, provided food and helped address side‐effects. Almost all women with adherence partners would recommend this strategy to others. Adherence partners are an acceptable, low‐cost strategy with the potential to support antenatal micronutrient supplementation adherence.